ACADEMIC RESILIENCE AND SELF-ESTEEM AS DETERMINANT OF STUDENTS’ ACADEMIC PERFORMANCE IN ZAMFARA STATE - Chioma Ifeoma Ojeleye; Oluchi Nnadozie Adegbile; Taibat Apanpa (Milestone: Journal of Strategic Management, 2023)
The academic performance of students in the nations tertiary institutions has been on the decline. The study explored self-esteem and academic resilience as determinants of students’ academic performance in Federal Polytechnic Kaura-Namoda, Zamfara state. The study employed survey and cross-sectional research design. The study employed purposive sampling technique as 800 pieces of questionnaire were administered students in the institution out of which 682 were valid and used for the analyses. The study used statistical package for social sciences (SPSS) to run the preliminary analyses such as detection of missing value, outliers, multicollinearity and test of normality. Structural equation model (SmartPLS) was used to run the measurement and structural models. The findings revealed that self-esteem and academic resilience have positive and significant effect on students’ academic performance in Federal Polytechnic Kaura-Namoda, Gusau, Zamfara state. The study recommended that educational stakeholders (the government, school management, lecturers and school peers) should encourage students to bounce-back from seemly difficult situation to stimulate their performance.